The social world(s) of the platonic dialogues. Preliminary considerations for a research project - Molnár, Gábor (Acta Scientiarum Socialium, 2011)
The article proposes a research project to reconstruct Socratic philosophical activity as embedded in its social (basically micro-social) environment. As research in the sociology of philosophical activities, it can prepare the way for a subsequent analysis of Socratic philosophy in terms of the sociology of philosophical knowledge. After arguing for the necessity of this research for a proper understanding of Socratic philosophy, the paper surveys some of the epistemological and methodological problems and tasks to be faced if one wants to realize the program. It distinguishes the notion of historical sociological fidelity from that of historical factual fidelity. It also distinguishes between different senses of the opposition of internal and external factors in the field of inquiry (different but not unrelated senses, one could say senses nested in one another): ideas (ideal sense-formations) vs. the real activities in which they are instantiated, mental vs. bodily activities, individual vs. social activities, foreground vs. background activities, activities central vs. peripheral to the philosophical thinking processes, and, finally, activities and ideas internal vs. external to the field of philosophy. In all cases, it is stated, the demarcating activities and the border-crossing phenomena are the most important subjects of investigation. As for the units of sociological analysis, from a micro-sociological perspective they can be classified in three levels: the individual, the interactional, and the supra-interactional. The most important units to be analyzed at the individual level are the individuals’ life-history, way of life, personality, social roles, ego-network and capitals. At the supra-interactional level, the dyadic relationships, social groups, organizations, networks, milieus, and local communities are to be investigated.